APPLICATION OF MUSCLE INHIBITING TECHNIQUES TO CHILDREN WITH CEREBRAL PALSY - Mariya Gramatikova (Peytchinski Publishing, 2020)
Purpose: The research aims to conduct a pilot study and monitor the effectiveness of a method of muscle-inhibition techniques applied to soft tissue contractures of the hip complex in children with cerebral palsy. Material/Methods: eight children with spastic quadriparesiswere studied by means of goniometric measurements, palpatory evaluations of the muscle tone, and tests to detect myo-articular contractures in the hip complex. The test battery was applied on the children both before and after they had gone through 30-day physiotherapy that included sessions of myo-articular mobilisation, post-isometric relaxation and stretching. Each of the muscleinhibiting techniques was applied 6-8 times, accompanied by stretching in the final range that continued until the co-contraction disappeared, followed by re-stretching enabled by the gained volume of movement in the joint. The duration of the stretching varied from one child to the next depending on the extent of activation of the Golgi reflex. At the maximum range of motion, the stretch hold was about 50-60 seconds. Results: The results of the study show that X of the passive hip extension on the first day was 3.7°+4.282, indicating its severe limitation. After the 30-day physiotherapy, the mean values reached 12,19°+4,07°, in other words, the indicator had improved by 8,44°+4,07°. On the first day, passive flexion of X=103.1°+ 13.77° was established in the hip joint; in the second study, this value was X = 120.0°+ 10.17°. Flexibility in the hip joint increased by 16.9°. The abduction in the joint on the first day of the study had values of X=20.94+7.793, which by the 30th day had increased to 36.25+8.466. P-values indicate that the physiotherapy model applied had resulted in statistically significant differences in the test parameters. Conclusion: The applied method of muscle-inhibition techniques is effective in children with spastic quadriparesis and restores the soft tissue and articular mobility of the hip complex.